The impact of food poverty on educational achievement: a New Zealand case study in global context - McKelvie Sebileau, Pippa; Swinburn, Boyd; de Seymour, Jamie (Frontiers in Education, 2025)
Hunger negatively impacts a student’s ability to engage and learn at school. Rising food poverty among school students across the globe is increasingly recognized as a critical factor impacting educational achievement. International assessments show a consistent and strong link between student hunger and lower academic performance, yet detailed analysis remains limited. The aim of this paper is to quantify the impact of student hunger on educational attainment. We use New Zealand as a case study, a high-income country with surprisingly high levels of food poverty. We carry out a cross sectional study of New Zealand data from three large-scale educational datasets comparing student achievement scores with self-reported food insufficiency at home. We observed a consistent, repeated and large effect size, with students experiencing hunger showing a learning gap of up to 4 years compared to their peers. This effect holds constant even after adjusting for student socio-economic status. Overall, these large dataset results demonstrate how being hungry at school and/or home is a major barrier to learning and that structural changes to reduce poverty, as well as programmatic responses such as free school lunches, must become national education priorities.